Proposed observational study protocol for early differentiation of cytokine release syndrome and sepsis in CAR-T recipients with haematological malignancies using the IL-6/PCT ratio: the DRACARYS study - Ibraheem, Anas; Dalby, Melanie (Frontiers in Oncology, 2025)
Chimeric Antigen Receptor T-cell (CAR-T) therapy has revolutionised treatment for haematological malignancies, demonstrating remarkable efficacy in B-cell leukaemias, lymphomas, and multiple myeloma. However, severe toxicities—particularly Cytokine Release Syndrome (CRS) and sepsis—present significant clinical challenges. Both conditions share overlapping features, including fever, hypotension, and multi-organ dysfunction, making timely and accurate differentiation essential. CRS is driven by excessive cytokine release, predominantly IL-6, and is treated with IL-6 receptor blockade (tocilizumab) and corticosteroids. Sepsis, by contrast, results from a dysregulated immune response to infection and requires antibiotics, as well as supportive care. Due to diagnostic uncertainty, clinicians often treat both conditions empirically. This can lead to inappropriate therapies—immunosuppressives may worsen sepsis, while antibiotics in CRS contribute to antimicrobial resistance and unnecessary healthcare burden. Existing biomarkers, such as IFN-γ and IL-1β, have shown potential but are limited by cost, availability, and the lack of rapid bedside implementation. There is a pressing need for a clinically accessible and reliable biomarker to distinguish CRS from sepsis in CAR-T patients. We hypothesise that the IL-6/procalcitonin (PCT) ratio will improve diagnostic accuracy. IL-6 is elevated in both conditions, while PCT is more specific to bacterial infection. However, PCT alone may be unreliable in immunocompromised patients, such as those receiving CAR-T therapy. The IL-6/PCT ratio is expected to reduce inter-individual variability and address limitations inherent to each marker when used alone. In this multi-centre, observational, prospective study, we will evaluate the IL-6/PCT ratio in febrile CAR-T patients. The primary analysis will focus on relapsed/refractory B-cell lymphomas, with a prespecified expansion/validation across other CAR-T indications. Clinical adjudication will serve as the standard of reference. We will assess diagnostic performance using Receiver Operating Characteristic (ROC) analysis to determine sensitivity, specificity, and optimal cutoffs. This study, titled DRACARYS (Differentiating Reactions—CRS versus sepsis—After CAR-Ts), aims to enhance diagnostic precision, guide timely and appropriate treatment, and reduce complications and unnecessary healthcare utilisation in CAR-T recipients.